DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LERANERS - Abdullayeva Diyora; alolova M (TADQIQOTLAR, 2025)
Annotation: The given thesis describes the significant changes in the impact of education on the mental development of young school-age children, and some of the problems they face in understanding themselves, and some issues they face in learning foreign languages and some methodological recommendations for solving them.